If I Could Keep You Little... - Richmond, Marianne (Naperville, IL : Sourcebooks Jabberwocky, 2012)
Parents imagine what they would continue to do with their children if they could only keep them from growing up, but also realize all the wonderful things they would miss as their children reached various milestones on their own.
Cover title.
Reprint. Originally published: c2010.
New Kids Book 2023 Fall.
Ages 3 and up.
AD440L
Decoding demand: 53 (medium) Semantic demand: 56 (medium) Syntactic demand: 77 (high) Structure demand: 33 (low)
Keywords: Board books -- Juvenile fiction; Parent and child -- Juvenile fiction; Growth -- Juvenile fiction; Stories in rhyme -- Juvenile fiction; Board books; Board books; Fiction